2002
DOI: 10.1046/j.1420-9101.2002.00449.x
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative population divergence in proximate determination of a sexually selected trait in the collared flycatcher

Abstract: We examined proximate determination of sexually selected forehead patch size in a Central-European population of Ficedula albicollis, the collared flycatcher, using a 9-year database, and compared our results with those obtained in other populations of the same and the sister species. Betweenindividual variation of forehead patch size was large, its repeatability larger than, and heritability similar to the Swedish population. Unlike in the other populations, the trait proved unaffected by body condition, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
81
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(94 citation statements)
references
References 98 publications
(140 reference statements)
8
81
5
Order By: Relevance
“…Whereas studies in a population in Gotland, Sweden, showed that the size of this trait was a good indicator of phenotypic quality (Gustafsson et al 1995;Qvarnström 1999; also see Gustafsson and Qvarnström 2006), this is not the case in our population (Hegyi et al 2002(Hegyi et al , 2006a, although the trait is an important determinant of social mating success (Hegyi et al 2010). The male forehead patch size was estimated as the product of its maximum height and maximum width.…”
Section: Study Species and Field Methodsmentioning
confidence: 53%
See 3 more Smart Citations
“…Whereas studies in a population in Gotland, Sweden, showed that the size of this trait was a good indicator of phenotypic quality (Gustafsson et al 1995;Qvarnström 1999; also see Gustafsson and Qvarnström 2006), this is not the case in our population (Hegyi et al 2002(Hegyi et al , 2006a, although the trait is an important determinant of social mating success (Hegyi et al 2010). The male forehead patch size was estimated as the product of its maximum height and maximum width.…”
Section: Study Species and Field Methodsmentioning
confidence: 53%
“…This species is ideal for long-term studies of reproductive success. It shows a preference for nestboxes, can easily be captured, and has high breeding-site fidelity (Pärt and Gustafsson 1989;Könczey et al 1992;Hegyi et al 2002) and considerable local recruitment rates (Pärt 1990;Török et al 2004). Nestboxes were checked multiple times a week throughout the nesting period, so breeding attempts were followed from nest building to fledging.…”
Section: Study Species and Field Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Potti, 1993;Morales et al, 2007). Once that genetic and environmental contributions to ornament size in blackand-white European Ficedula species are beginning to be understood (Sheldon et al, 1997;Qvarnströ m, 1999;Hegyi et al, 2002;Saetre et al, 2003;Saether et al, 2007; this study), the biggest challenge is now for researchers to explain the within and between-population differences in the degree of inhibition (Williams and Carroll, 2009) of ornament displaying in females, a trait that we show is apparently subject to large environmental/nonadditive genetic variance(s). When optimal trait expression differs between the sexes, between-sex population variation in its degree might cause geographically variable antagonistic selection , wherein genetic factors spread across populations by giving a reproductive advantage to males while disadvantaging females or vice versa.…”
Section: Discussionmentioning
confidence: 75%